2022
DOI: 10.1017/hpl.2023.6
|View full text |Cite|
|
Sign up to set email alerts
|

High-power 1560 nm single-frequency erbium fiber amplifier core-pumped at 1480 nm

Abstract: High power continuous-wave single frequency Er-doped fiber amplifiers at 1560 nm by in-band and core pumping of a 1480 nm Raman fiber laser are investigated in detail.Both co-and counter-pumping configurations are studied experimentally. Up to 59.1 W output and 90% efficiency were obtained in fundamental mode and linear polarization in the co-pumped case, while less power and efficiency were achieved in the counter-pumped setup for additional loss. The amplifier performs indistinguishably in terms of laser lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…These imperfections lead to a rapid increase in fiber-end reflectivity. Studies have shown that the error of surface roughness and angles resulting from precision machining is 20 dB more than the theoretical value [16]. Therefore, when cutting the fiber-end surface, the insertion loss should be increased by more than 60 dB by matching the refractive index of the outside medium and fiber core.…”
Section: Principles Of Fiber-end Antireflectionmentioning
confidence: 99%
“…These imperfections lead to a rapid increase in fiber-end reflectivity. Studies have shown that the error of surface roughness and angles resulting from precision machining is 20 dB more than the theoretical value [16]. Therefore, when cutting the fiber-end surface, the insertion loss should be increased by more than 60 dB by matching the refractive index of the outside medium and fiber core.…”
Section: Principles Of Fiber-end Antireflectionmentioning
confidence: 99%
“…Another limiting factor of the EYDF-based SFFA is the serious thermal issue that arises from its significant quantum defect, which is nearly ∼40% [72,73] . To address this problem, tandem pumping the amplifier at ∼1480 nm with Raman fiber amplifiers or erbium-doped fiber amplifiers (EDFAs) at ∼1530 nm would be helpful, although currently the achievable output power is limited by the available pump power [74,75] . In addition, it is noted that the SBS is currently not the major restriction for the power scaling of 1.5 μm SFFAs, with which the TMI effect has not even been experimentally observed.…”
Section: Free-space Couplingmentioning
confidence: 99%
“…High-power narrow linewidth single-frequency lasers have attracted extensive interest due to their superior characteristics in some fields, such as gravitational wave detection [1] , quantum information optics [2] , atomic physics [3] and nonlinear frequency conversion [4][5][6] . The most widely used approaches to obtain high-power narrow linewidth lasers are master oscillator power amplification (MOPA) structures based on low-power narrow linewidth seeds [7,8] and single-cavity structures with direct high-power output [9,10] . However, in MOPA systems, aside from the problems of beam quality deterioration and mode instability due to thermal accumulation [11] , the linewidth broadening introduced by spontaneous radiation during the amplification process cannot be ignored.…”
Section: Introductionmentioning
confidence: 99%